Stopping the Virus; Study on Participatory Journalism and Digital Humanitarian during a Non-Natural Disaster in Indonesia - Nusantara, Samiaji Bintang; Rinaldi, Ingki; Veronika, Veronika (Jurnal Kajian Jurnalisme, 2024)
Philanthropic initiatives during disaster events have become embedded in Indonesian society. It also manifests in a digital humanitarian practice during the COVID-19 pandemic, categorized by the government as a non-natural disaster from 2020 to 2023. The spreading of misinformation and inaccurate data on cases of COVID-19 patients, have become an obstacle in the early stages of efforts to stop fatalities. As the government imposes lockdown and restrictions access to information, the news media as one of the key sources of information is under attack. Thus, citizen initiatives in stopping the pandemic are worth documented as a lesson learned when managing disasters in the future. By conducting qualitative method, this research describes the implementation of participatory journalism in practice related to the data gathering and reporting on COVID-19 cases in Indonesia by "LaporCovid-19" and "KawalCOVID19". This research finds both platforms carry out digital humanitarian practices while organizing citizens and producing, curating, and disseminating information. As the government imposes lockdown and restricted access toward media and journalists, the digital humanitarian practice involves citizens through decentralization, self-organization, volunteerism, and the optimization of digital platforms. The collaboration is a multidisciplinary subject that combines crises management, communications, network collaborative organizational structures, social computing and technology. In conclusion, their efforts offer a model to develop citizen participation in the non-natural disaster using digital apps and citizen resources. The model intertwines participatory journalism and digital humanitarian practices that engage citizens during the pandemic on both digital platforms contribute to other citizens' efforts to prevent and overcome health crises.